2019
DOI: 10.1038/s41598-019-41579-2
|View full text |Cite
|
Sign up to set email alerts
|

3D ITO-nanowire networks as transparent electrode for all-terrain substrate

Abstract: A 3D ITO nanowire network with high quality by using polystyrene as an assisted material has been prepared, demonstrating superior optoelectronic performances with a sheet resistance of 193 Ω/sq at 96% transmission. Both remarkable flexibility tested under bending stress and excellent adhesion applied on special terrain substrate have been achieved. This method has led to a full coverage of micro-holes at a depth of 18 µm and a bottom spacing of only 1 µm, as well as a perfect gap-free coverage for micro-tubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…[21][22][23] Thus, Table 3 includes the comparison with reported methods and protocols for the fabrication of ITO thin films and low dimensional materials. 16,[21][22][23][26][27][28][28][29][30]71 First of all, although we produce polycrystalline nanotubes, the results of the single-wire electrical characterization support that the high crystalline quality and good connectivity between ITO grains forming the NTs shells allow an effective carrier transport along the NT length. Besides, in the above examples, all the nanotubes are domed, however, the same procedure can be modified to generate open-ended nanotubes by simply increasing the temperature rate slope during the evacuation of the organic template (see additional information elsewhere).…”
Section: Electrical Characterization Of Layers and Single Ntsmentioning
confidence: 96%
See 2 more Smart Citations
“…[21][22][23] Thus, Table 3 includes the comparison with reported methods and protocols for the fabrication of ITO thin films and low dimensional materials. 16,[21][22][23][26][27][28][28][29][30]71 First of all, although we produce polycrystalline nanotubes, the results of the single-wire electrical characterization support that the high crystalline quality and good connectivity between ITO grains forming the NTs shells allow an effective carrier transport along the NT length. Besides, in the above examples, all the nanotubes are domed, however, the same procedure can be modified to generate open-ended nanotubes by simply increasing the temperature rate slope during the evacuation of the organic template (see additional information elsewhere).…”
Section: Electrical Characterization Of Layers and Single Ntsmentioning
confidence: 96%
“…[63][64][65][66][67][68][69][70] Common shortcomings of these efforts are narrow spectral bands and complex fabrication procedures with limited scalability for large-area applications. 29 Recently, several authors have reported alternative solutions based on the formation of one-dimensional nanomaterials such as carbon nanotubes, Si nanoarrays, Cu nanowires, and ITO nanowires. 29 In our case, the characteristics of the supported nanotubes and nanotrees allow the straightforward use of these nanomaterials in a lithography-free process and on a broad variety of substrates without additional processing, patterning, or special optical arrangements.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inversion of signs of the real parts of the permittivity components in different RBs inside the mid- and far-IR ranges configures a hyperbolic dispersion for SnO 2 . Moreover, polar nanometer-sized crystals of SnO 2 ribbons or nanobelts (SnO 2 -NBs) 21 23 have been reported as key elements in gas sensors 24 , solar cells 25 , lithiation electrodes 26 – 28 , photonic devices 29 , flexible and transparent electrodes 30 , water treatment catalysts 31 , electrochemically active layers in hydrogen peroxide production 32 , and photocatalysis 33 . This is mainly due to their unique optical 21 , 24 and electronic 34 , 35 properties and large surface to volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a development of nanomaterial-based semiconductor caused dynamic progress in fabrication of more advanced electronic systems [ 1 , 2 , 3 ]. Indium-tin oxide (ITO), a heavily doped and highly degenerated n-type semiconductor with high carrier concentration (~10 21 cm −3 ) [ 4 , 5 , 6 ], is one of the most widely used transparent conductive oxides (TCO) due to unique combination of excellent electrical conductivity, optical transparency and good mechanical properties and relatively good chemical stability [ 7 , 8 , 9 ]. Although various new materials, such as tin dioxide (SnO 2 ) [ 10 ], zinc oxide (ZnO) [ 11 , 12 ], indium zinc oxide (IZO) [ 13 ], conductive nano-silver wire [ 14 ], have been applied in industry, ITO is still the main choice for conductive optical [ 15 ].…”
Section: Introductionmentioning
confidence: 99%